(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This study examines the impact of local governance on public safety, crime prevention, and community policing strategies. Through a mixed-methods approach, including qualitative interviews with local officials and quantitative analysis of crime data, the research identifies key governance practices that enhance community safety. Findings indicate that decentralized decision-making, community engagement, and inter-agency collaboration significantly reduce crime rates and improve public trust in law enforcement. The study underscores the importance of local governance in shaping effective crime prevention strategies and fostering safer communities.